Lipid-based nanosystems as carriers increasing the potential of selected berry polyphenol representatives - Lasoń, Elwira; Pokigo, Julia (Chemical and Process Engineering, 2025)
The aim of the study was to obtain stable systems of lipid-based nanocarriers (SLN, NLC, HA-NLC, liposomes) with a selected berry polyphenol – quercetin as an active ingredient. Lipid-based nanosystems were obtained using ultrasonification technique. The stability was assessed by macro- and microscopic observation and viscosity measurements. The physicochemical properties of both incorporated and nonincorporated carriers were examined with dynamic light scattering technique (DLS). In vitro release studies of quercetin were performed using cellulose membrane and the mixture of PBS/ethanol as an acceptor solution. The lowest average particle size was achieved for the traditional NLC formulation and ranged between 126:5 ± 1:6 nm for unloaded and 138:7 ± 1:0 nm for NLC with quercetin. Release study of the active ingredient from optimal lipid-based nanocarriers indicated its prolonged and controlled release profile. On this basis, a mathematical model that best describes the kinetics of the active substance release from the tested carriers was fitted. According to the results, the best fit of quercetin release from examined nanocarriers was obtained for the Higuchi model. The conducted research gave promising results allowing to conclude that the obtained lipid-based nanosystems may be potential carriers for quercetin which possess a therapeutic effect in the treatment of skin disorders.